The Design of Video-on-Demand Servers - Sumari, Putra; Kamarulhaili, Hailiza (Malaysian Journal of Computer Science, 2005)
Video on demand (VOD) system is an electronic video-rental service over a computer network. It provides users a service to browse and watch any video at any time with VCR (rewind, forward and pause) operations. One of the requirements for VOD system implementation is to have a VOD server that acts as an engine to deliver videos from the server’s disk to users. Designing VOD server, particularly the video layout component on the server’s disk, is an interesting issue as it determines the number of streams being delivered to users. Video blocks should be laid intelligently with less latency on disk and hence produce high number of streams. However, due to real time and large volume characteristics possessed by the video, the designing of video layout is a challenging task. Real time constraints the distribution of blocks on disk and hence decrease the number of streams being delivered to users. Another important aspect of designing video layout is the VCR operation service since it provides interactivity. It possesses the same challenge as in streaming videos to users as it consumes bandwidth of the server. In this paper we present a new video layout scheme for a VOD server called Disk-region storage scheme. The scheme partitions the disks into regions and uses a special algorithm to distribute blocks of video data within regions. The scheme is capable of producing a high number of streams as well as providing VCR operations to users. The simulation showed that the scheme increases the number of simultaneous stream by 15%. The scheme is also being designed with a simple one-way data retrieval mechanism and has a good load balancing on an array of disks.